Artificial intelligence in communication management: a cross-national study on adoption and knowledge, impact, challenges and risks. Issue 4 (7th May 2020) - Zerfass, Ansgar; Hagelstein, Jens; Tench, Ralph
Abstract : Purpose: Artificial intelligence (AI) might change the communication profession immensely, but the academic discourse is lacking an investigation of the perspective of practitioners on this. This article addresses this research gap. It offers a literature overview and reports about an empirical study on AI in communications, presenting first insights on how professionals in the field assess the technology. Design/methodology/approach: A quantitative cross-national study among 2, 689 European communication practitioners investigated four research questions: RQ1 – How much do professionals know about AI and to what extent are they already using AI technologies in their everyday lives? RQ2 – How do professionals rate the impact of AI on communication management? RQ3 – Which challenges do professionals identify for implementing AI in communication management? RQ4 – Which risks do they perceive? Findings: Communication professionals revealed a limited understanding of AI and expected the technology to impact the profession as a whole more than the way their organisations or themselves work. Lack of individual competencies and organisations struggling with different levels of competency and unclear responsibilities were identified as key challenges and risks. Research limitations/implications: The results highlight the need for communication managers to educate themselves and their teams about the technology and to identify the implementation of AI as a leadership issue. Originality/value: The article offers the first cross-national quantitative study on AI in communication management. It presents valuable empirical insights on a trending topic in the discipline, highly relevant for both academics and practitioners.